An eco-friendly and new facile method for synthesis of prenylated or geranylated acylphloroglucinol-based xanthenones - Tamil Segaran, Raaginie; Ng, Chean Hui; Mohd Aluwi, Mohd Fadhlizil Fasihi; Lam, Kok Wai; Shaari, Khozirah; Md Pisar, Mazura (Elsevier, 2024)
The synthesis of prenylated or geranylated acylphloroglucinol-based xanthenones with 15.1–36.9% yield was achieved via aldol condensation of 2,4,6-trihydroxy-3-prenylacetophenone (tHPA) or 2,4,6-trihydroxy-3-geranylacetophenone (tHGA) and 2-hydroxybenzaldehyde derivatives in the presence of lithium bis(trimethylsilyl)amide (LiHMDS) as deprotonating agent. This study is one of the first to report on the synthesis of xanthenones using strong non-nucleophilic base catalyst, and the described synthesis not only achieved a compound with a natural product skeleton but also formed in a simple and environmentally friendly specificity.